Yam dormancy: potential mechanisms for its manipulation - Barker, D.J.; Keatinge, J.D.H.; Asiedu, Robert (1999)
Tuber dormancy is of major importance in yam production, but the lack of a method to consistently break dormancy restricts the rate at which new clones can be multiplied to release to farmers. Much of the work on yam tuber dormancy was small scale, using only one or two clones and a few tubers. Often, the effects of a treatment on dormancy were seen as a side issue, and results were essentially anecdotal. Many chemicals were used in attempts to manipulate dormancy and although some success was achieved using gibberellic acid, this large amount of work yielded few future leads. Similarly, physical methods might be able to break yam dormancy but these studies have been unsystematic and inconsistent. Appropriate research directions are needed if yam breeding is to make progress and keep pace with food demands.